VASYL STEFANYK’S SHORT STORY «THE BABY WATCHER» AS TRANSLATED INTO GERMAN: A LINGUISTIC AND PRAGMATIC FACET - Lepokhin, Eugene (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Aim. This paper examines the translation of Vasyl Stefanyk’s short story «The Baby Watcher» (1921) into German. The purpose of the paper is to analyse the target text sentences’ syntactic structure in the remit of considering the equivalent and adequate rendering of the meaning of the original. Methods. In the furtherance of this purpose, we resorted to descriptive method (we identified the units of analysis in each individual sentence or its part under consideration), contrastive method (we compared the communicative and pragmatic correspondence of the translation to semantically equivalent units of the original) and the method of intent analysis (we determined the communicative intention of the speaker in free direct and indirect discourses). Results. Proceeding from the analysis of the lexical and stylistic features of the translation done by Alla Paslavska and Tobias Vogel, we argue that it renders the content of the original with appropriate / similar means, except when stylistically neutral target language lexemes are equivalent to the dialectally marked vocabulary of the source language. Originality. The paper is the first attempt for a syntactic analysis of the short story «The Baby Watcher», focusing on the pragmatic correspondence of the texts being compared. Practical significance. The findings of the study will serve to those involved in the synchronic-comparative study of language systems, the study of the Ukrainian writer’s signature world-view for the purposes of producing fiction translation, as well as at the decision of linguistic pragmatics applied tasks.